2005
DOI: 10.1097/01.dad.0000158294.23630.ef
|View full text |Cite
|
Sign up to set email alerts
|

Monster Cells in Malignant Melanoma

Abstract: Cells with significantly enlarged nuclei have been described in basal cell carcinomas, dermatofibromas, and pleomorphic fibromas, to name a few. These cells are typically visible using low power microscopy and have been termed "pleomorphic" or "monster cells." They have not been previously described in cutaneous melanomas. We sought to determine the prevalence of monster cells in otherwise conventional biopsies of primary cutaneous melanomas and its association with other histopathologic features of this malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In this case, immunohistochemical staining was utilized to support a diagnosis of melanoma, in addition to providing information about tumor behavior. To explore whether monster cells represent actively proliferating cells, Boyd et al stained two melanomas with monster cells for MIB‐1 and found negative staining of monster cells, with surrounding tumor cell positivity . In the current case, the tumor cells (including monster cells) were strongly and diffusely positive for MIB‐1, indicating active proliferation of these cells.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this case, immunohistochemical staining was utilized to support a diagnosis of melanoma, in addition to providing information about tumor behavior. To explore whether monster cells represent actively proliferating cells, Boyd et al stained two melanomas with monster cells for MIB‐1 and found negative staining of monster cells, with surrounding tumor cell positivity . In the current case, the tumor cells (including monster cells) were strongly and diffusely positive for MIB‐1, indicating active proliferation of these cells.…”
Section: Discussionmentioning
confidence: 67%
“…The use of the term ‘monster cells’ has since been used to describe findings in other cutaneous proliferations including malignancies such as basaloid squamous cell carcinoma, basal cell carcinoma and melanoma; in contrast to the original descriptor, monster cells in these malignancies show prominent mitotic activity. The term was first utilized to characterize cells in melanomas in the identification of 13 cases of melanoma with monster cells in a case series by Boyd et al in 2005 . Previously, terms such as ‘pleomorphic’ or ‘anaplastic’ signified melanomas with cells containing large, bizarre and hyperchromatic nuclei with atypical mitotic figures, which typically stain positively with immunohistochemical markers of melanoma such as S‐100, NKI‐C3 and HMB‐45.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Giant cell melanoma 4,6,27,28 Uncommonly, primary or secondary melanomas may be composed almost entirely of multinucleated pleomorphic tumour giant cells (''monster cells''). IHC is essential for confirmation of the diagnosis and exclusion of a host of other malignant neoplasms that can exhibit similar morphology, especially if melanin pigment is sparse or absent, or if an intra-epidermal component is lacking.…”
Section: Spitzoid (Spitz-like) Melanoma 59e13mentioning
confidence: 99%
“…12 Many of the clinical and histologic features seen in these and other variants of dermatofibromas have clinicopathologic overlap with unrelated and often more insidious lesions. Not only are vascular and melanocytic lesions often considered in the differential diagnosis both clinically and histologically [13][14][15] but also a variety of melanocytic lesions have been reported to arise in association with dermatofibromas. 16,17 Osteoclast-like giant cells 18 and ossification 19 are features that have been described in dermatofibromas.…”
Section: Introductionmentioning
confidence: 99%